2021
DOI: 10.1016/j.ijhydene.2020.03.202
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of yttrium promotion on Ni-layered double hydroxides-derived catalysts for hydrogenation of CO2 to methane

Abstract: Ni-containing mixed oxides derived from layered double hydroxides with various amounts of yttrium were synthesized by a co-precipitation method at constant pH and then obtained by thermal decomposition. The characterization techniques of XRD, elemental analysis, low-temperature N 2 sorption, H 2 -TPR, CO 2 -TPD, TGA and TPO were used on the studied catalysts. The catalytic activity of the catalysts was evaluated in the CO 2 methanation reaction performed at atmospheric pressure. The obtained results confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Positive effects induced by yttrium on the textural properties of different types of supports were also reported in the literature. 39,43,44 Świrket al 43 studied the effect of Y on Ni-based double layered hydroxides for dry reforming of methane and found that doping Y inside the matrix promotes the increase of specific surface area. Similar results were also found for Ce and Y modified double layered hydroxides, showing that higher SSA, pore volume and pore size were obtained over Y-modified catalyst compared to those of Ce-promoted material without the presence of Y.…”
Section: Textural Properties Structural Parameters and Chemical Vs Surface Compositions Of The Catalystsmentioning
confidence: 99%
“…Positive effects induced by yttrium on the textural properties of different types of supports were also reported in the literature. 39,43,44 Świrket al 43 studied the effect of Y on Ni-based double layered hydroxides for dry reforming of methane and found that doping Y inside the matrix promotes the increase of specific surface area. Similar results were also found for Ce and Y modified double layered hydroxides, showing that higher SSA, pore volume and pore size were obtained over Y-modified catalyst compared to those of Ce-promoted material without the presence of Y.…”
Section: Textural Properties Structural Parameters and Chemical Vs Surface Compositions Of The Catalystsmentioning
confidence: 99%
“…Catalytic conversion of CO 2 to chemicals and fuels plays a significant role in CCU technologies. Accordingly, carbon dioxide can be converted to syngas [6][7][8], methane [9][10][11], methanol [12], higher alcohols [13], diethyl ether [14] through a large variety of reactions. Hydrogenation of carbon dioxide, and CO 2 methanation in particular, has attracted attention of the academic community due to its numerous advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal-based catalytic systems, such as Ni [9,16], Co [17], Pd [18], and Rh [19] based catalysts were found promising in the reaction. Among these catalytically active materials, Ni-based catalysts have attracted the most attention due to their numerous advantages, such as high availability, low cost, and high activity and selectivity [20].…”
Section: Introductionmentioning
confidence: 99%
“…CH 4 is highly valuable as a fuel, because of its high energy density (23 625 MJ m –3 , liquefied), serving as synthetic natural gas (SNG) 10 . In the process known as Power‐to‐Gas (PtG), CH 4 may be used as a hydrogen carrier, obtained via renewable energy sources such as biomass, wind, and solar, which generate electricity that is used for electrolysis of H 2 O to obtain H 2 , to be finally converted to CH 4 as it is easier and safer for both storing and transporting than H 2 11–13 …”
Section: Introductionmentioning
confidence: 99%
“…Concerning metal promotion, some researches has focused on known active metals such as Fe and Co to boost activity and selectivity, or alkali and alkaline‐earth such as Na, Mg, and Ca, and lanthanides such as La, to improve basic properties and enhance CO 2 adsorption due to its mild acidic nature 13,27–31 . Although these additives may also help to maintain properties such as low particle size and resistance to sintering, carbon deposition, and poisoning, some attempts with Cu promotion have been made in order to improve catalysts resistance.…”
Section: Introductionmentioning
confidence: 99%